1995
DOI: 10.1016/s0022-5347(01)66870-8
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infection in Prostatodynia

Abstract: In a subset of prostatodynia patients bacteria may have an etiological role. Antibiotic treatment demonstrated clinical efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…A large study of 597 prostatitis patients indicated that nearly one-third were diagnosed with prostatodynia, which is a significant fraction of the urological population (10). The recent literature suggests that the condition referred to as chronic idiopathic (nonbacterial) prostatitis may actually have an infectious etiology (18,32,38,53). Some patients relate the onset of their symptoms to sexual activity-sometimes associated with acute urethritis (7)-while others have indicated no relationship with sexual activity.…”
Section: Definition Of a Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…A large study of 597 prostatitis patients indicated that nearly one-third were diagnosed with prostatodynia, which is a significant fraction of the urological population (10). The recent literature suggests that the condition referred to as chronic idiopathic (nonbacterial) prostatitis may actually have an infectious etiology (18,32,38,53). Some patients relate the onset of their symptoms to sexual activity-sometimes associated with acute urethritis (7)-while others have indicated no relationship with sexual activity.…”
Section: Definition Of a Problemmentioning
confidence: 99%
“…Gram-positive bacteria, particularly the cocci, remain controversial as possible etiologic agents. Recently, coagulase-negative staphylococcal species and coryneforms have been found in segmented specimens (including prostatic secretions) and are postulated to play a role in chronic idiopathic prostatitis (38,53). It is generally agreed that Enterococcus faecalis can cause chronic bacterial prostatitis and related recurrent enterococcal bacteriuria.…”
Section: Common Bacterial Etiologic Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…No other differences were found. Lowentritt et al [30] also performed a case-control study of 22 patients and 16 controls. Nine patients with CPPS and six controls had positive cultures.…”
Section: Control Populationsmentioning
confidence: 99%